(untitled) (مجلة المنصور, 2022)
Due to the recent growth in the importance of Web applications, and their adoption as a main alternative for computer applications, and since they provide a shortcut in resources, centralized processing and database, in addition to ease of maintenance and update of a single server rather than a number of computers could reach into thousands. Therefore in this paper was focused on building web applications using .Net framework and the programming languages used are (C# & Java Script) being the two languages hard to penetrate and easily linked to the database, especially for applications that need giant databases and error free data retrieval. Note that the platform providing the .Net framework is a solid platform that has a wide range of security and compatibility capabilities. In this paper, website of Ministry Of Higher Education And Scientific Research has been designed and built, with database design and implement ,using Microsoft SQL Server to build the structure of the system. In addition the report viewer is used to view the contents of the database that can be converted to Pdf and Excel.